Recurrent primary intracranial myxofibrosarcoma: a case report and review of the literature - Wen, Shuting; Tu, Mengqi; Liao, Rufang; Li, Huan (Frontiers in Oncology, 2026)
Primary intracranial myxofibrosarcoma (MFS) is an exceedingly rare mesenchymal malignancy, with only a few cases reported. We report a 34-year-old male with a right frontal lobe MFS who subsequently developed two non-contiguous recurrences in the right temporal and left frontal lobes. Histopathological examination revealed a stepwise progression from low- to intermediate- to high-grade disease, accompanied by progressively increasing Ki-67 labeling indices. Notably, the pattern of spatially separate recurrences suggests the possibility of cerebrospinal fluid–mediated dissemination. This case highlights the aggressive and heterogeneous nature of intracranial MFS and underscores the importance of long-term, comprehensive follow-up to detect recurrences, particularly at non-contiguous sites.